Antiretrovirals, Fractures, and Osteonecrosis in a Large International HIV Cohort. (22nd February 2017) - Borges, Álvaro H.; Hoy, Jennifer; Florence, Eric; Sedlacek, Dalibor; Stellbrink, Hans-Jürgen; Uzdaviniene, Vilma; Tomazic, Janez; Gargalianos-Kakolyris, Panagiotis; Schmid, Patrick; Orkin, Chloe; Pedersen, Court; Leen, Clifford; et al.
Summary: We investigated the association of exposure to antiretroviral drugs with incident fractures and osteonecrosis of the femoral head in the EuroSIDA cohort. We demonstrated that past and current exposure to tenofovir disoproxil fumarate, but no other antiretroviral, was independently associated with higher incidence of fractures. After mutual adjustment, no antiretroviral was associated with osteonecrosis risk. Abstract: Background: Antiretrovirals (ARVs) affect bone density and turnover, but their effect on risk of fractures and osteonecrosis of the femoral head is less understood. We investigated if exposure to ARVs increases the risk of both bone outcomes. Methods: EuroSIDA participants were followed to assess fractures and osteonecrosis. Poisson regression identified clinical, laboratory and demographic predictors of either bone outcome. Ever, current, and cumulative exposures to ARVs were assessed. Results: During 86118 PYFU among 11820 included persons (median age 41y, 75% male, median baseline CD4 440/mm 3, 70.4% virologically suppressed), there were 619 fractures (incidence/1000 PYFU 7.2; 95% CI 6.6–7.7) and 89 osteonecrosis (1.0; 0.8–1.3). Older age, white race, lower BMI, IV drug use, lower baseline CD4, HCV coinfection, prior osteonecrosis, prior fracture, cardiovascular disease, and recent non-AIDS cancer (last 12 months) were associated with fractures. After adjustment, persons who had ever used tenofovir disoproxil fumarate (TDF) (1.40; 1.15–1.70) or who were currently on TDF (1.25; 1.05–1.49) had higher incidence of fractures. There was no association between cumulative exposure to TDF and fractures (1.08/5 y exposure; 0.94–1.25). No other ARV was associated with fractures (all P > .1). Risk of osteonecrosis was associated with white race, lower nadir CD4, prior osteonecrosis, prior fracture, and prior AIDS. After mutual adjustment, no ARV was associated with osteonecrosis. Conclusions: In human immunodeficiency virus (HIV) infection, host factors, HIV-specific variables, and comorbidities contribute to risk of fractures and osteonecrosis. Exposure to TDF, but not other ARVs, was an independent risk factor for fractures.